Distribution of Megabenthos Associated with Seagrass Meadows at Batu Jimbar Beach, Sanur, Denpasar, Bali - Muji Wasis Indriyawan; I Gusti Ngurah Agung Dhananjaya; Constantein Petta; Edwin Jefri (Jurnal Biologi Tropis, 2026)
Seagrass meadows are important coastal ecosystems that provide habitat, feeding grounds, and nursery areas for a wide range of marine organisms, particularly benthic taxa such as Mollusca, Arthropoda, Echinodermata, and Annelida. Batu Jimbar Beach, located in the eastern part of Denpasar, Bali, supports relatively extensive seagrass coverage. Despite its ecological importance, information on the spatial distribution of megabenthos associated with seagrass meadows in this area remains limited. This study aimed to assess the spatial distribution of megabenthos associated with seagrass meadows at Batu Jimbar Beach, Sanur, Denpasar, Bali. Seagrass coverage was estimated using remote sensing (Sentinel-2B imagery with water column correction) and megabenthos data were collected via quadrat transect method. A total seagrass area of 94.31 ha was recorded; the community comprised 28 genera from five phyla. Synapta was the most widely distributed genus, found at 11 of 13 stations. Seagrass meadows at Batu Jimbar Beach support a relatively diverse megabenthic community with heterogeneous spatial distribution patterns influenced by seagrass coverage and substrate variability. These findings provide baseline data essential for the management and conservation of coastal ecosystems in Bali.